Smart Intelligent Computing and Applications Proceedings of the Second International Conference on SCI 2018, Volume 2 - Satapathy, Suresh Chandra; Bhateja, Vikrant; Das, Swagatam; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The proceedings covers advanced and multi-disciplinary research on design of smart computing and informatics. The theme of the book broadly focuses on various innovation paradigms in system knowledge, intelligence and sustainability that may be applied to provide realistic solution to varied problems in society, environment and industries. The volume publishes quality work pertaining to the scope of the conference which is extended towards deployment of emerging computational and knowledge transfer approaches, optimizing solutions in varied disciplines of science, technology and healthcare.
Keywords: Telecommunication; Quantitative research; Artificial intelligence; Communications Engineering, Networks; Data Analysis and Big Data; Artificial Intelligence